Study some of the reconstruction experiences and their suitability with humanitarian need: دراسة بعض تجارب إعادة الإعمار وتلاؤمها مع الاحتياجات الإنسانية - Nour Mtaneous Abboud (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
Wars and armed conflicts are one of the most important threats to the social, cultural, economic and political structures of the countries that have been afflicted and thus cause damage at all levels. Urban and architectural damage may be the living record of wars and conflicts. At the forefront is the destruction of architecture and urbanization associated with society, which represents the memory and identity of this community, In particular the destruction of architecture, which generally includes different types of buildings depicting the climax of humanitarian activities at different periods of history. Each type of buildings has a special nature that imposes a different method of dealing with them. It depends on the importance of the building and its historical value. Destruction so that reconstruction is physically adequate for the population.